Z Analisa Keandalan Turbin Uap Dengan Penerapan Total Productive Maintenance (TPM) Dan 4 Disipline Of Execution Di Pabrik Kelapa Sawit - Zulham Effendi zulham; Siti Aisyah; Muhammad Bagas (Jurnal Biogenerasi, 2026)
A steam turbine is an energy conversion machine whose converted energy is used by other machines to generate power. This study aims to analyze the reliability of turbine engines using the Total Productive Maintenance (TPM) method and the 4 Disciplines of Execution (4DX). In this study, TPM was used to identify various major causes of production time loss, such as breakdowns, setup time, and loading time. Meanwhile, 4DX focuses on achieving key objectives through consistent and measurable actions, namely zero breakdowns and zero stagnation. The results of this study indicate that the Availability value is 98.69%, the Performance value is 98.14%, the Quality value is 99.74%, and the OEE value is 96.61%, which means that the turbine is in a reliable condition. In addition, 4DX plays a role in accelerating the achievement of improvement targets by providing a more focused approach, monitoring daily activities, and enhancing accountability. The research results indicate that the combination of these two methods is effective in improving turbine reliability, extending equipment lifespan, and fostering employee discipline. Keywords: Steam Turbine, Reliability, TPM, OEE, 4DX